THE IMPLEMENTATION OF SDG-ORIENTED PROJECTS IN EFL INSTRUCTION: A DESCRIPTIVE QUALITATIVE REVIEW - Hasibuan, Kalayo; Fadhila Akbar Damanik, Reyziq; Aalya Frhsty, Bianca; Sri Hafsah, Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The integration of Sustainable Development Goals (SDGs) into English as a Foreign Language (EFL) instruction has received growing attention as part of efforts to promote sustainability-oriented education. This study aims to examine the implementation of SDG-oriented projects in EFL instruction, their pedagogical benefits, challenges, and implications for teaching practice. Employing a descriptive qualitative design through library research, the study analyzed journal articles, books, conference proceedings, and official documents related to SDGs, Education for Sustainable Development (ESD), Project-Based Learning (PBL), and EFL instruction. The findings reveal that SDG-oriented projects are primarily implemented through Project-Based Learning (PBL), Digital Project-Based Learning (DPBL), collaborative learning activities, classroom discussions, and sustainability-oriented instructional materials. These approaches contribute to the development of students’ language skills, critical thinking, global awareness, intercultural competence, digital literacy, and social responsibility. However, their implementation remains constrained by limited teacher preparedness, insufficient instructional resources, technological limitations, and the uneven representation of sustainability themes in learning materials. The study highlights the importance of contextualized learning practices, teacher professional development, and institutional support to facilitate the effective integration of SDGs into EFL instruction.